The Effects of Teaching the Communication Skills to Patients Through Role-Playing Method on Nursing Students\' Self-Efficacy - fatemeh karbasi; Mahnaz khatiban; Alireza Soltanian (Hamadan University of Medical Sciences, 2019)
Introduction: Teaching the professional communication skills can be effective in developing the learners' self-efficacy. In the patients' training with communication skills, the active and student-centered learning methods, such as role-playing, are emphasized. Therefore, this study was run to determine the effects of applying the role-playing method to communication education on the self-efficacy and communication skills of nursing students.   Methods: This controlled before-after quasi-experimental study was conducted in Hamadan University of Medical Sciences in 2015. Out of 15 student groups, four groups were randomly assigned to the role-playing (n=32) and four groups to the routine (n=32). Sherer's self-efficacy questionnaire was completed by students at the beginning and end of clinical education. Patient-nurse communication program training through role-playing method was implemented during the interval period. Data analysis was run using SPSS16 by statistical tests at 95% confidence level.   Results: Students in the role-playing group were compared to the conventional group in terms of the individual characteristics (P >0.05). At the baseline, the control group had higher self-efficacy than those in the role-playing group (P<0.05). But after the intervention, analysis of covariance showed that the significant progress was only made in the role-playing students' self-efficacy compared to the control group when baseline score differences were controlled (P<0.001).   Conclusion: Using an active role-playing method can lead to self-efficacy of undergraduate nursing students in comparison with the traditional method.